2007
DOI: 10.1375/twin.10.1.127
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Genetic Study of Plasma Lipids in Adolescent Twins

Abstract: P lasma lipids such as high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol and triglyceride levels contribute to variation in the risk of cardiovascular disease. The early stages of atherosclerosis in childhood have also been associated with changes in triglycerides, LDL and HDL. Heritability estimates for lipids and lipoproteins for adolescents are in the range .71 to .82, but little is known about changes of genetic and environmental influences over time in adolescence. We have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…There were no strong associations across age groups; however, this is not inconsistent with previous reports, which have suggested that different genetic factors may act upon these phenotypes at different times [25,35]. The increased number of large test statistics relative to the expected distribution for the association with triacylglycerol suggests that common mitochondrial variants may influence this trait in early adolescence.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…There were no strong associations across age groups; however, this is not inconsistent with previous reports, which have suggested that different genetic factors may act upon these phenotypes at different times [25,35]. The increased number of large test statistics relative to the expected distribution for the association with triacylglycerol suggests that common mitochondrial variants may influence this trait in early adolescence.…”
Section: Discussionsupporting
confidence: 52%
“…The heritability estimates for each trait in our sample are high (Table 4), due to the heritability being estimated under an AE model, and there are strong phenotypic correlation across the three measurement time points [25,35,39]. Table 5 shows the most significant associations for each trait in the 12, 14 and 16 year age groups.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…They can also test whether nonshared environmental effects are solely a consequence of measurement error and biological variation, or also reflect relatively long-term differences in the individual environment. Data on LDL and HDL cholesterol, and triglycerides, have been presented elsewhere (Middelberg et al, 2007). The aims of the present report are to use repeated-measures data for biochemical variables associated with obesity (uric acid, ALT, AST, GGT) to investigate first, whether the genes affecting these traits vary with age in adolescence; and second, whether nongenetic (environmental) effects persist over time.…”
Section: A Longitudinal Genetic Study Of Uric Acid and Liver Enzymes mentioning
confidence: 99%
“…This study also found that low birth weight was associated with blood pressure, total and low-density lipoprotein cholesterol, and fibrinogen within DZ but not MZ twin pairs, suggesting an additional genetic influence on these associations (41). A longitudinal adolescent twin study (125 MZ and 166 DZ pairs) involving 965 families, however, found little evidence of shared environment effects on the variation in lipids, except high-density lipoprotein cholesterol, and only minimal effects of nonshared environment (42). A twin study involving 174 twin pairs showed that maternal alcohol exposure during pregnancy was associated with increased carotid-femoral pulse wave velocity but not with systolic or diastolic blood pressure or child adiposity measures (e.g., BMI) at 9 y (43).…”
Section: Do Twins Always Share An Equal Environment?mentioning
confidence: 57%